IMPLEMENTASI METODE YANBU’A UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN MAHASANTRI MA’HAD AL-JAMI’AH UIN RADEN INTAN LAMPUNG - Etika Afdila; Umi Hijriyah; Baharudin; Uswatun Hasanah (Pascasarjana Universitas Al-Qolam Malang, 2025)
The re-implementation of the rector's decision for KIP Kuliah scholarship students to live in Ma'had al-Jami'ah has provided the latest findings that not all scholarship students are good at reading the Qur'an, this is one of the real evidences that there are still many UIN Raden Intan Lampung students who still cannot read the Qur'an, and has caused changes in the process of implementing the yanbu'a method at Ma'had al-Jami'ah UIN Raden Intan Lampung. This study aims to determine how the implementation of the yanbu'a method at Ma'had al-Jami'ah UIN Raden Intan Lampung in improving the ability to read the Qur'an of students, especially KIP Kuliah scholarship students who are required to live in Ma'had al-Jami'ah. This study uses a descriptive qualitative method with a type of field research, and data collection techniques are observation, interviews and documentation. The findings of this study are that the yanbu'a method is able to provide significant changes in improving the ability to read the Qur'an of students who do not come from Islamic boarding schools and whose initial Qur'an reading scores are quite low. Based on the results of interviews with students and also the mu’alim/ah who teach halaqoh, there are supporting and inhibiting factors in learning the Qur’an using the yanbu’a method. The curriculum at Ma’had al-Jami’ah includes various academic and extracurricular activities that aim to develop students’ skills both academically and morally. The application of the yanbu’a method at Ma’had al-Jami’ah has achieved its goal of improving students’ ability to read the Qur’an.